Development of a Novel Contactless Mechanocardiograph Device - Kouhyar Tavakolian; Faranak M. Zadeh; Yindar Chuo; Ali Vaseghi; Bozena Kaminska (International Journal of Telemedicine and Applications, 2008)
A novel method of detecting mechanical movement of the heart, Mechanocardiography (MCG), with no connection to the subject's body is presented. This measurement is based on radar technology and it has been proven through this research work that the acquired signal is highly correlated to the phonocardiograph signal and acceleration-based ballistocardiograph signal (BCG) recorded directly from the sternum. The heart rate and respiration rate have been extracted from the acquired signal as two possible physiological monitoring applications of the radar-based MCG device.